2011
DOI: 10.1039/c1py00311a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hierarchical porous polypyrrole nanoclusters and their application for removal of Cr(vi) ions in aqueous solution

Abstract: Hierarchical porous polypyrrole (PPy) nanoclusters composed of small PPy nanospheres were successfully prepared in one-step by a reactive-template method without any surfactants. The Fe 3 O 4 nanoclusters acted as both the template for shaping PPy structure and oxidant source simultaneously. The dosage of pyrrole monomer, the concentration of HCl acid had significant influence on the structures and conductivities of the resulting PPy nanoclusters. By carefully controlling the experimental conditions, hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…The SEM micrographs of (a) Fe 3 Figure 2 presents the FTIR absorption spectra of PAMpDA, Fe 3 O 4 , and PAMpDA@Fe 3 O 4 nanocomposite. It is clear that the copolymer and nanocomposites showed very similar spectra.…”
Section: Sem Micrographsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM micrographs of (a) Fe 3 Figure 2 presents the FTIR absorption spectra of PAMpDA, Fe 3 O 4 , and PAMpDA@Fe 3 O 4 nanocomposite. It is clear that the copolymer and nanocomposites showed very similar spectra.…”
Section: Sem Micrographsmentioning
confidence: 99%
“…15,16 Magnetic adsorbents are usually composed of the magnetic cores to ensure a strong magnetic response and a polymeric shell to supply favorable functional groups for various applications. 17,18 The objective of current research is to prepare metal-chelating conductive polymer, poly(aniline-co-m-phenylenediamine) (PAMpDA), and its superparamagnetic poly(aniline-co-mphenylenediamine)@Fe 3 O 4 (PAMpDA@Fe 3 O 4 ) nanocomposite as adsorbents for the removal of risky heavy metals ions such as Pb(II), Cd(II), and Co(II) ions from aqueous medium. In this research, PAMpDA copolymer and PAMpDA@Fe 3 O 4 nanocomposite were synthesized by chemical oxidative polymerization and in situ coprecipitation technique, respectively.…”
mentioning
confidence: 99%
“…Yao et al [21] prepared hierarchical porous PPy nanoclusters for the removal of Cr(VI) ions in aqueous solution and observed that removal capacity of PPy nanoclusters was higher than that of traditional PPy nanoparticles owing to their larger surface area. Moreover, for enhanced removal of Cr(VI) from aqueous solutions, Bhaumik et al [22,23] synthesized PPy/ Fe 3 O 4 magnetic nanocomposite and PPy-PANI nanofibers.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, conducting polymers have been proven to be promising materials for the adsorption of Cr(VI) from aqueous solutions (Bhaumik et al, 2011;Yao et al, 2011). Availability, easy preparation and functionalisation have made them highly desirable in many applications.…”
Section: Introductionmentioning
confidence: 99%